Adoption of full-culm bamboo as a mainstream structural material - Kent A. Harries (npj Materials Sustainability)
Abstract Widespread adoption of minimally processed bamboo materials has significant potential to reduce emissions and energy use in the global construction sector. Such adoption is hindered by the significant variation inherent in bamboo material properties and the relative dearth of available data in this field. This paper provides one perspective to overcoming these hurdles through a proposed approach of materials informatics used to inform context-appropriate building material and design standards.